STRATEGI PENGUATAN PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA DI DESA BAHOI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Cindy ., Triananda; Audrey Julia Maria Maweikere; Meisje Yellie Memah (Sam Ratulangi University, 2021)
This study aims to develop strategies that can be used to strengthen community participation in ecotourism development in Bahoi Village, West Likupang District, North Minahasa Regency. This research was carried out from April to May 2021. The data collected in the study were primary data obtained directly from the Bahoi Village Head, Pokdarwis Chair, Bahoi Marine Protected Area Management Head and community representatives from each guard through interviews and questionnaires. Secondary data were obtained from the Bahoi Village Office. Sampling was done by purposive sampling, namely 15 samples. The analytical method used in this research is SWOT analysis. The concept of measuring variables in this study is that strength is the superiority of the form of participation owned by the people of Bahoi Village; weakness is the lack form of community participation in Bahoi Village; opportunity is a condition that can benefit the Bahoi Village community in increasing their participation; Threats is a conditions that can harm or hinder the Bahoi Village community in increasing their participation.